CRIMINAL DISPOSAL OF THE DEAD AFTER HOMICIDAL STRANGULATION: AUTOPSY DEFYING PUTREFACTION AND EVIL MOTIVES ONCE AGAIN - MITTAL, PAWAN; CHAWLA, RAHUL; KUMAR MALIK, ANIL (Innovare Journal of Medical Sciences, 2021)
Homicide with concealment of the corpse is a rarely encountered phenomenon in routine forensic work. Such cases represent a challenge by the fact that the bodies or parts thereof are unknown, without any relevant history, and usually depict well-established changes of putrefaction at autopsy. However, a proper scrutiny of the circumstances along with discovery of significant injuries at autopsy may bring a breakthrough to the case. A case of putrefied and unidentified male dead body is hereby described that was killed by ligature strangulation followed by dumping into a deep water channel which was, however, preceded by tying-up of extremities with a strong metallic chain. The postmortem findings along with the ancillary investigations and case circumstances helped in concluding the cause and manner of death which was subsequently followed by the arrest of the perpetrators who submitted and explained the whole story of the crime. Various possible means of suicide, including a self-application of restraint, were excluded from the study.